THE DEVELOPMENT OF '99 CAHAYA DI LANGIT EROPA' MOVIE NARRATION FOR SPIRITUAL EDUCATION (PENGEMBANGAN NARASI FILM '99 CAHAYA DI LANGIT EROPA' UNTUK PENDIDIKAN SPIRITUAL) - Wiruma Titian Adi; Andika Hendra Mustaqim (Leksema: Jurnal Bahasa dan Sastra, 2017)
The objective of this research was to explore and develop the narration of a religious movie 99 Cahaya di Langit Eropa in Indonesia to be applied in spiritual education at schools. This research applied qualitative method using content analysis and narratology approach. The result of the research was the development the movie narration which was focused on plot, performance or presentation, and focalization telling the interactions of the main characters with Westerners who are sentimental with Islam due to the issues of terrorism and the efforts to explain the position of Islam as a compassionate religion. The development of religious film narratives in Indonesia for spiritual education at schools should be based on everything related to spirituality.